CHANGING OF STUDENT'S MENTAL MODEL ABOUT VIRUS THROUGH MICROBIOLOGY COURSE PROGRAM BASED ON MENTAL MODEL - Yanti Hamdiyati; Fransisca Sudargo; Sri Redjeki; Any Fitriani (EDUSAINS, 2018)
PERUBAHAN MODEL MENTAL MAHASISWA PADA POKOK BAHASAN VIRUS MELALUI PROGRAM PERKULIAHAN MIKROBIOLOGI BERBASIS MODEL MENTAL  AbstractThis study aims to analyze changes in mental models of students on the subject of the virus through mental model based-microbiology course. The research method is pre-experiment with one-group pretest-posttest design. Respondents of this research consists of 5 semester students of Biology education program at UPI Biology Education Department of 39 students. The mental model based-microbiology course consists of several stages (syntax). The mental modeling instrument uses concept maps, while the students' perceptions of the lecture program use a closed and open questionnaire. Data obtained in the form of concept maps before and after lectures on the subject of the virus. Concept maps are then analyzed by reference concept map. Quantitative data of the concept map is converted into qualitative data to determine the level of mental model, namely: emergent = score 1, transitional = score 2, close to extended = score 3, and complete (extended) = score 4. Questionnaire about the research program shows the change of mental model level on the subject of the virus before the implementation of the mental model based-microbiology course. is at emergent and transition level. After the implementation of the mental model based-microbiology course is at the transitional level and close to extended. This indicates an increase in the level of mental models of students through the mental model based-microbiology course. AbstrakPenelitian ini bertujuan untuk menganalisis perubahan model mental mahasiswa pada pokok bahasan virus melalui program perkuliahan Mikrobiologi Berbasis Model Mental (MBM2). Metode penelitian yang dilakukan adalah pre- experiment dengan disain penelitian one-group pretest - postest design.  Responden penelitian ini terdiri dari mahasiswa semester 5 program studi pendidikan Biologi di Departemen Pendidikan Biologi UPI sebanyak 39 mahasiswa.  Program Perkuliahan MBM2 terdiri dari beberapa tahapan (sintaks). Instrumen model mental menggunakan peta konsep, sedangkan persepsi mahasiswa tentang program perkuliahan menggunakan angket tertutup dan terbuka. Data yang diperoleh berupa peta konsep sebelum dan setelah perkuliahan pada pokok bahasan virus. Peta konsep selanjutnya dianalisis berdasarkan peta konsep rujukan. Data kuantitatif peta konsep diubah menjadi data kualitatif untuk menentukan level model mental, yaitu : berkembang (emergent) = skor 1, peralihan (transitional) = skor 2,  mendekati lengkap (close to extended) = skor 3, dan lengkap (extended) = skor 4. Hasil penelitian menunjukkan perubahan level model mental pada pokok bahasan virus sebelum implementasi program perkuliahan MBM2 ada pada level berkembang (emergent)  dan peralihan (transitional) . Setelah implementasi program perkuliahan MBM2 ada pada level peralihan (transitional) dan mendekati lengkap (close to extended). Hal ini menunjukkan adanya peningkatan level model mental mahasiswa melalui program perkuliahan MBM2.Permalink/DOI:http://dx.doi.org/10.15408/es.v10i1.7777